Inclusive Education Practice in Southwestern Nigeria: A Situational Analysis - Adeniyi, Samuel Olufemi; Adeyemi, Akinkunmi Oluwadamilare (Journal of the American Academy of Special Education Professionals, 2015)
This study presented situational analysis of inclusive educational practice in southwestern Nigeria. The study employed descriptive survey research design. Samples of 131 teachers, 51 parents and 51 head teachers/principals were purposively selected from State Grammar School, Ipakodo Junior Grammar School, Methodist Grammar School, Ijokodo High School and St. Peter College in Southwestern Nigeria. Three research questions were answered. A questionnaire tagged inclusion assessment inventory with reliability coefficient of 0.71 was used to collect data. The data collected were analyzed using frequency counts and simple percentage. The results revealed positive attitude of teachers and negative disposition on the parts of government and parents to inclusive education practice in Southwestern Nigeria. Strong advocacy and reorientation were recommended.